Stymulanty rozwoju innowacyjności w regionach polski na przykładzie działalności badawczo-rozwojowej - Grabowska, Aleksandra (Stimulant of Innovation Development in Poland's Regions on the Example of Research & Development Activity, 2006)
Innovation is one of the crucial activities in European Union. It is introduced in the main sectors of market economy f.e. services or industry. There are many advantages of innovation-.diversification of goods, better quality, opening new markets, better work's conditions etc. It helps not only economy development, but it is also one of these elements, that shape and improve regional attractive Offer. This paper presents the stimuli of innovation in Poland's regions and the research & development activity an example of them.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 409-417